Evaluasi Fenotipe dan Pendugaan Parameter Genetik Beberapa Galur Jagung Pakan (Zea Mays L.) - Naufal Ardiansyah; Aptika Hana Prastiwi Nareswari; Edy Kustiani; Junaidi Junaidi (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The advancement of plant breeding technology continues to accelerate, with the selection of parental lines becoming a pivotal component of precision breeding. This study aims to evaluate the phenotypic diversity and genetic parameters of 20 feed maize lines across two distinct environments. The research was conducted at two locations with varying altitudes: Location 1 (50 m asl) and Location 2 (600 m asl), utilizing a Randomized Complete Block Design (RCBD) with two replications per site. Parameters observed encompassed both quantitative and qualitative traits. Data were subjected to Analysis of Variance (ANOVA), followed by cluster analysis using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) to determine the phylogenetic distances between lines. The results revealed significant differences (p < 0.05) across all quantitative characters, with Variety 9 demonstrating superior performance in the majority of parameters. Cluster analysis categorized the genotypes into several groups with a minimum genetic distance of 1.732, indicating their potential utility in the development of superior hybrid varieties.